Penerapan Model Pembelajaran Moving Class Untuk Meningkatkan Semangat Belajar Anak di TK ‘Aisyiyah Kertek - Fatma Fatma; Vava Imam Agus Faisal (STAI AL-AMIN, 2026)
This study aims to describe the implementation of the moving class learning model and the factors influencing learning enthusiasm among early childhood students at TK ‘Aisyiyah Kertek. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that the moving class model effectively increases children’s learning enthusiasm, as reflected in improved independence, interest, motivation, and active participation in learning activities. A dynamic, varied, and enjoyable learning environment encourages children to be more enthusiastic in learning. The success of the moving class implementation is influenced by internal factors such as mood, interest, potential, and physical and psychological conditions of the children, as well as external factors including teacher roles, facilities and infrastructure, classroom arrangement, teacher creativity, and peer interaction.